2021
DOI: 10.3390/pathogens10010044
|View full text |Cite
|
Sign up to set email alerts
|

Liver Abnormalities after Elimination of HCV Infection: Persistent Epigenetic and Immunological Perturbations Post-Cure

Abstract: Chronic hepatitis C (CHC) is a major cause of hepatocellular carcinoma (HCC) worldwide. While directly acting antiviral (DAA) drugs are now able to cure virtually all hepatitis C virus (HCV) infections, even in subjects with advanced liver disease, what happens to the liver and progression of the disease after DAA-induced cure of viremia is only beginning to emerge. Several large-scale clinical studies in different patient populations have shown that patients with advanced liver disease maintain a risk for dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 88 publications
1
7
0
1
Order By: Relevance
“…Our data show an improvement in these immune and liver disease biomarkers in plasma (immune exhaustion (PD1), chemokines (CXCL10, CCL2, and CXCL8), and cytokines (IL10)) after achieving SVR with DAA therapy in HIV/HCV-coinfected individuals. These results are similar to those found in HCV-monoinfected persons, in whom immune and liver function improved after HCV clearance by DAA, although normalization of the immune system after SVR is not always achieved ( 54 , 55 ). Regarding HIV/HCV-coinfected patients, there are limited data on their status following DAA therapy.…”
Section: Discussionsupporting
confidence: 86%
“…Our data show an improvement in these immune and liver disease biomarkers in plasma (immune exhaustion (PD1), chemokines (CXCL10, CCL2, and CXCL8), and cytokines (IL10)) after achieving SVR with DAA therapy in HIV/HCV-coinfected individuals. These results are similar to those found in HCV-monoinfected persons, in whom immune and liver function improved after HCV clearance by DAA, although normalization of the immune system after SVR is not always achieved ( 54 , 55 ). Regarding HIV/HCV-coinfected patients, there are limited data on their status following DAA therapy.…”
Section: Discussionsupporting
confidence: 86%
“…Our data suggest that ANGPTL-3 may be one of many genes belonging to the host transcriptome, secretome, epigenome and immunome that retain their expression levels after successful HCV eradication in patients with advanced liver damage. These genes are believed to be part of a residual HCV fingerprint that has been suggested to promote hepatocarcinogenesis in some cured patients [ 21 , 22 , 63 , 64 ]. Surprisingly, similar persistently expressed immunoregulatory signatures were even discovered in acutely infected HCV patients who received early DAA treatment [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the HCV-mediated reprogramming of the host metabolism, epigenome and immunity and the constant deregulation of cellular signalling and hepatic gene expression lead to the establishment of a viral fingerprint that persistently remains after viral eradication. It is thought that these alterations may collectively promote HCC development and progression depending on the extent of the existing liver damage in some cured patients [ 9 , 10 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hamdane et al showed that epigenetic changes in H3K27ac levels are induced through direct interaction between HCV and hepatocytes and indirectly through liver fibrosis [59]. Importantly, several studies show that these changes persist after sustained viral response (SVR) to either DAAs or interferon-based therapies [60][61][62].…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%